PERBEDAAN JUMLAH KOLONI BAKTERI PATOGEN PADA GAGANG PINTU BERDASARKAN WAKTU, LOKASI, DAN RUANGAN DI RUANG INTENSIF RSUP DR. M. DJAMIL PADANG - Faisaelia, Rezka Nanda; Rasyid, Roslaili; Sulastri, Delmi; Linosefa, Linosefa; Hardisman, Hardisman; Hasmiwati, Hasmiwati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Objective: This study aims to determine differences in pathogenic bacterial contamination on door handles based on time, location, and room in the intensive care unit of Dr. M. Djamil Hospital; Methods: This type of research is observational analytic. Samples were taken in 5 intensive rooms with a total of 40 samples. After that, the number of colonies was calculated based on differences in sampling time, door handle location, and room; Results: The results showed that 87.5% of door handles in the intensive care unit of Dr. M. Djamil Hospital were contaminated with bacteria. The bacteria found were S.warneri, S.hom.hominis, A.viridans, S.vitulinus, and S.maltophilia; Conclusion: There is no significant difference in the number of bacterial colonies on the door handles of the intensive care unit of Dr. M. Djamil Hospital based on time, location, and room.